Radiation exposure induces genome-wide alternative splicing events in Aedes aegypti mosquitoes - Harley Bendzus-Mendoza; Amanda Rodriguez; Tathagata Debnath; C. Donovan Bailey; Hailey A. Luker; Immo A. Hansen (Scientific Reports)
Abstract Sterile insect technique is a method to control insect pest populations by sterilizing males with ionizing radiation. However, radiation sickness lowers the fitness of sterilized males. In this study, we investigate impacts of ionizing radiation on gene transcription, specifically alternative splicing events in irradiated male Aedes aegypti mosquitoes. We compared RNA sequencing data from mosquitoes irradiated with a single standard X-ray dose of 50 Grey and un-irradiated control mosquitoes using the Multivariate Analysis of Transcript Splicing computational tool. We found that radiation exposure caused alternative splicing events in 197 genes that are involved in a variety of biological processes including the Hippo and Notch cell signaling pathways. Our results suggest that radiation damage produced by ionizing radiation can alter the splicing of genes involved in important biological functions in male Ae. aegypti mosquitoes. These findings identify several new leads for new projects aimed at understanding the impact of radiation-induced alternative splicing on mosquito fitness and improving sterile insect technique by the development of radio-resistant mosquito strains.